SELENILAÇÃO DIRETA DA LIGAÇÃO C(sp2)-H DE IMIDAZO[2,1-b]TIAZOL NA PRESENÇA DE PERÓXIDO DE HIDROGÊNIO DE URÉIA (PHU) E LACTATO DE ETILA: UM PROTOCOLO AMBIENTALMENTE BENIGNO - RAFAELY BIANCA CARVALHO SANTOS (2024)
Organic synthesis plays a crucial role in investigating compound structures and chemical reactions, as well as creating new compounds. The development of new methodologies, especially for the synthesis of heterocyclic compounds, has been promising due to their applicability in pharmacology, agrochemistry and materials industry. Therefore, it is essential to develop safer, cleaner and greener methodologies. Heterocyclic compounds, when functionalized through the insertion of a chalcogen into the structure, such as selenium, generate a C-Se bond with responsible biological activities, responsible for antioxidant, antibacterial and anticancer actions. This work proposes a sustainable and safe methodology for a specific heterocyclic, imidazothiazole. As it has an important biological activity, the present work aims to investigate and propose a more sustainable and safe methodology within the scope of green chemistry. The reaction process is based on a single step of direct selenylation of the C(sp2)-H bond of imidazo[2,1-b]thiazole in the presence of urea hydrogen peroxide as catalyst and ethyl lactate as solvent, both with characteristics safe, economical and sustainable at 60 °C for 3 h of reaction. The methodology presents favorable reaction conditions, with high yield. Furthermore, expanding the scope to several imidazole derivatives was investigated, totaling 27 examples and yields between 52 and 94%, in addition to easy gram-scale performance and metal-free conditions. Finally, the present research significantly contributes to the frontier of knowledge for studies of organoselenium molecules with desired biological activities.